Diabetes and pre‐diabetes in patients with heart failure and preserved ejection fraction. (4th January 2022) - Jackson, Alice M.; Rørth, Rasmus; Liu, Jiankang; Kristensen, Søren Lund; Anand, Inder S.; Claggett, Brian L.; Cleland, John G.F.; Chopra, Vijay K.; Desai, Akshay S.; Ge, Junbo; Gong, Jianjian; Lam, Carolyn S.P.; et al.
Abstract : Aim: There is an association between heart failure with preserved ejection fraction (HFpEF) and insulin resistance, but less is known about the diabetic continuum, and in particular about pre‐diabetes, in HFpEF. We examined characteristics and outcomes of participants with diabetes or pre‐diabetes in PARAGON‐HF. Methods and results: Patients aged ≥50 years with left ventricular ejection fraction ≥45%, structural heart disease and elevated N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) were eligible. Patients were classified according to glycated haemoglobin (HbA1c): (i) normal HbA1c, <6.0%; (ii) pre‐diabetes, 6.0%–6.4%; (iii) diabetes, ≥6.5% or history of diabetes. The primary outcome was a composite of cardiovascular (CV) death and total heart failure hospitalizations (HFH). Of 4796 patients, 50% had diabetes and 18% had pre‐diabetes. Compared to patients with normal HbA1c, patients with pre‐diabetes and diabetes more often were obese, had a history of myocardial infarction and had lower Kansas City Cardiomyopathy Questionnaire scores, while patients with diabetes had more clinical evidence of congestion, but similar NT‐proBNP concentrations. The risks of the primary composite outcome (rate ratio [RR] 1.59, 95% confidence interval [CI] 1.35–1.88), total HFH (RR 1.67, 95% CI 1.39–2.02) and CV death (hazard ratio [HR] 1.35, 95% CI 1.07–1.71) were higher among patients with diabetes, compared to those with normal HbA1c. Patients with pre‐diabetes had a higher risk (which was intermediate between that of patients with diabetes and those with normal HbA1c) of the primary outcome (HR 1.27, 95% CI 1.00–1.60) and HFH (HR 1.35, 95% CI 1.03–1.77), but not of CV death (HR 1.02, 95% CI 0.75–1.40). Patients with diabetes treated with insulin had worse outcomes than those not, and those with 'lean diabetes' had similar mortality rates to those with a higher body mass index, but lower rates of HFH. Conclusion: Pre‐diabetes is common in patients with HFpEF and is associated with worse clinical status and greater risk of HFH. Clinical Trial Registration: ClinicalTrials.gov Identifier NCT01920711. Abstract : Patient characteristics and outcomes, according to diabetes status, and according to whether patients with diabetes were treated with insulin or not, in PARAGON‐HF. BMI, body mass index; CV, cardiovascular; HbA1c, glycated haemoglobin; HF, heart failure; HFpEF, heart failure with preserved ejection fraction.